Strengthening Parent’s Engagement Amidst Pandemic: A Grounded Theory (Faculty of Teacher Training and Education, Universitas Terbuka, 2021)
The study mainly focused on determining how the parents support and assist their children while studying at home because of the COVID-19 pandemic. It utilized qualitative research with grounded theory as an approach. Using one-on-one interviews, the researchers generated emerging themes from constant comparative analysis of data collected about parents' engagement in children's education in the new normal. Participants of this study were the 27 purposively chosen parents of Calamba Bayside Integrated School. The study was conducted during the school year 2020-2021. In this study, parents describe their experiences regarding their roles in delivering lessons to their children. It also explores the strategies or ways of parents in providing support and assistance to their children while learning at home. The researchers analyzed and interpreted these using initial coding, focused coding, theoretical coding, and axial coding. The results revealed that parents provide support and assistance in the education of their children. These are by sharing inputs, consistent guidance, and provision of their children's educational needs. On the other hand, the challenges experienced by them include parents' level of knowledge, parents' time constraints, and parents' diverse roles. The researchers generated the Theory of Evolving Parental Roles, which refers to the functions of parents in education in the new normal.